Case Report: Severe ARDS in a Pediatric Hematopoietic Stem-Cell Transplantation Recipient Caused by Disseminated Toxoplasmosis - de la Mata Navazo, Sara; Slöcker Barrio, María; García-Morín, Marina; Beléndez, Cristina; Escobar Fernández, Laura; Rincón-López, Elena María; Aguilera Alonso, David; Guinea, Jesús; Marín, Mercedes; Butragueño-Laiseca, Laura; López-Herce Cid, Jesús (Frontiers in Pediatrics, 2022)
Toxoplasma gondii infection is a severe complication of hematopoietic stem-cell transplantation (HSCT) recipients that can remain unnoticed without a high clinical suspicion. We present the case of a 6-year-old patient with acute lymphoblastic leukemia and HSCT recipient who was admitted to the Pediatric Intensive Care Unit (PICU) on post-transplantation day +39 with fever, hypotension, severe respiratory distress and appearance of a lumbar subcutaneous node. She developed severe Acute Respiratory Distress Syndrome (ARDS) and underwent endotracheal intubation and early mechanical ventilation. Subsequently, she required prone ventilation, inhaled nitric oxide therapy and high-frequency oscillatory ventilation (HFOV). An etiologic study was performed, being blood, urine, bronchoalveolar lavage and biopsy of the subcutaneous node positive for Toxoplasma gondii by Polymerase Chain Reaction (PCR). Diagnosis of disseminated toxoplasmosis was established and treatment with pyrimethamine, sulfadiazine and folinic acid started. The patient showed clinical improvement, allowing weaning of mechanical ventilation and transfer to the hospitalization ward after 40 days in the PICU. It is important to consider toxoplasmosis infection in immunocompromised patients with sepsis and, in cases of severe respiratory distress, early mechanical ventilation should be started using the open lung approach. In Toxoplasma IgG positive patients, close monitoring and appropriate anti-infectious prophylaxis is needed after HSCT.